Tendinopathy of the long head of the biceps tendon: histopathologic analysis of the extra-articular biceps tendon and tenosynovium - Streit, Jonathan J (Open Access J Sports Med, 2015)
BACKGROUND: Bicipital tendinitis is a common cause of anterior shoulder pain, but there is no evidence that acute inflammation of the extra-articular long head of the biceps (LHB) tendon is the root cause of this condition. We evaluated the histologic findings of the extra-articular portion of the LHB tendon and synovial sheath in order to compare those findings to known histologic changes seen in other tendinopathies. METHODS: Twenty-six consecutive patients (mean age 45.4±13.7 years) underwent an open subpectoral biceps tenodesis for anterior shoulder pain localized to the bicipital groove. Excised tendons were sent for histologic analysis. Specimens were graded using a semiquantitative scoring system to evaluate tenocyte morphology, the presence of ground substance, collagen bundle characteristics, and vascular changes. RESULTS: Chronic inflammation was noted in only two of 26 specimens, and no specimen demonstrated acute inflammation. Tenocyte enlargement and proliferation, characterized by increased roundness and size of the cell and nucleus with proteoglycan matrix expansion and myxoid degenerative changes, was found in all 26 specimens. Abundant ground substance, collagen bundle changes, and increased vascularization were visualized in all samples. CONCLUSION: Anterior shoulder pain attributed to the biceps tendon does not appear to be due to an inflammatory process in most cases. The histologic findings of the extra-articular portion of the LHB tendon and synovial sheath are similar to the pathologic findings in de Quervain tenosynovitis at the wrist, and may be due to a chronic degenerative process similar to this and other tendinopathies of the body.